MANAJEMEN RISIKOUSAHATANI JAMUR TIRAM PUTIH (PLEROTUS ASTREOTUS) DALAM UPAYA MEMPERTAHANKAN PENDAPATAN PETANI - Endah Djuwendah; Eka Septiarini (Paspalum: Jurnal Ilmiah Pertanian, 2016)
Horticulture is one of the subsectors of agriculture that has great prospects for development, it is associated with the number of horticultural varieties that have high economic value if properly cultivated.White oyster mushroom (Pleurotus astreatus) is one of the prospective horticulture commodities to be cultivated. Characteristics of white oyster mushroom both taste and nutritional content of the main attraction that drives demand.However, the development of farming oyster mushroom farming exposed to various risks. The purpose of this are  to identify the risks of farming oyster mushroom, describe farmer's perception of the risk and risk management of oyster mushroom farm. The research location in the village of Kertawangi, Cisarua district at West Bandung Regency. The research method used was survei. The primary data obtained through interviews with 39 farmers oyster mushroom, while secondary data obtained from the study of literature both from the mass media, research reports and related articles. The results showed that the risk of oyster mushroom farm in the village of Kertawangi Cisarua subdistrict consists of the production risk by 54 percent, the risk of 6- 7 percent and marketing and financial risk by 39 percent.Farmers about risk perception is all that is likely to prejudice the business, production and income instability, farmers believe the risks can be prevented or mitigated with good risk management practices and correct. Risk management is done by way of production diversification, marketing risks are managed dengana collecting market information and financial risks anticipated with supply of cash and credit from various financial institutions.